IMPLEMENTASI SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (SIAK) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MANADO - -, Lestari; Lengkong, Florence Daicy; Tampi, Gustaf Budi (Sam Ratulangi University, 2016)
Abstract: Implementation of Population Administration Information System is the implementationof a policy in a web-based system which is based procedures - the procedures and wear specialstandardization. In order to provide effective and efficient services, computerized services wasneeded. In support of the population administration to improve the quality of services performedeither by applying or using the information system of population administration. This study aimsto investigate the implementation of the information system of population administration in theDepartment of Population and Civil Registration Manado obstacles encountered along itsimplementation. The research method used was qualitative, where the technique used datacollection using interviews is to get the necessary information through oral communication directlywith the informant or informants. After interviews with 15 informants, further data collectiontechniques used were observation and documentation field. From the research that has been donein the Department of Population and Civil Registration Manado City can be seen that theimplementation of the Population Administration Information System (SIAK) has been going wellbut there are still obstacles and problems in the process.Keywords : Population Administration Information System Implementation (SIAK).